Harmonisasi Hubungan Wewenang Kepala Desa dengan Badan Perwakilan Desa (BPD) dalam Pembentukan PERDA - Syahbudin Syahbudin (Al-'Adl, 2017)
The resources of the village apparatus for the administration of village government are an integral part of the administration and management of village administration. The resource of the village administration apparatus is a fundamental aspect in relation to the formulation and formation of village regulations for the sake of the administration of the village administration in the management of the village regulations is not multi-interpretive and contradictory to the existing rules. In general, this study is directed to identify problems and constraints that arise, both in the aspect of formulating village regulations and in the management of those regulations in the community, and identifying how far the drafting of the village regulations is contrary to the regulations above them. Therefore, this study aims to find and find solutions to emerging problems related to village regulations, and to recommend to the District Government to immediately establish a Regional Regulation on the drafting guidelines and mechanisms for the preparation of village regulations. This aspect is a scientific recommendation prepared based on normative research so that it can be used as a reference for the Local Government in preparing the Regional Regulations on the preparation guidelines and mechanisms of village regulations that can be used as legal umbrella for all village apparatus in the District, with the aim to create management and good village governance.